The Western Australian Family Connections Genealogical Project: Detection of familial occurrences of single gene and chromosomal disorders - Brameld, Kate; Dye, Danielle; Maxwell, Susannah; Brisbane, Joanna; Glasson, Emma; Goldblatt, Jack; O'Leary, Peter (Mary Ann Liebert, Inc. Publishers, 2014)
Aim: To investigate using a Western Australian (WA) genealogical database for the identification of single gene and chromosome disorders among families. Method: Hospital admissions for single gene and chromosome disorders recorded during 2000–2006 were identified from the WA Hospital Morbidity Data System. The proportion of these conditions occurring in family groups was then identified using genealogical links created through the WA Family Connections Genealogical Project. Results: There were 216 family clusters among 11,303 people who were recorded as having a genetic or chromosomal disorder on their hospital admission record. The most common single gene conditions found to occur in multiple family members included blood clotting disorders such as Factor VIII deficiency and Von Willebrand’s disease, followed by cystic fibrosis, myotonic dystrophies, neurofibromatosis, tuberous sclerosis, and osteogenesis imperfecta. Discussion: Single gene disorders most commonly occurring in multiple family members have been identified using the WA Family Connections Genealogical Project. These disorders reflect the most common single gene disorders requiring hospital admission, but which are not fatal before reproductive age and do not result in a loss of fertility. They are also restricted to disorders with earlier onset, as the WA Family Connections Genealogical Project currently covers 2–3 of the most recent generations. This study demonstrates the utility of record linkage genealogies to identify kindred with genetic disorders, offering a rich resource of information for focused genetic epidemiological research.